2018
DOI: 10.1002/admt.201800133
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Ionic Sensitivity in Solution‐Gated Graphene‐Hexagonal Boron Nitride Heterostructure Field‐Effect Transistors

Abstract: surface optical phonons. [14] As a dielectric interface, SiO 2 limits carrier mobility, and increases current-voltage hysteresis. [13,15] With a wide band gap (5.97 eV) and layered hexagonal Bernal structure (1.7% lattice mismatch to graphene) with dangling bond-free chemically inert surface, hexagonal boron nitride (hBN) is a near-ideal dielectric interface to graphene. The goal of this study is to investigate the graphene ISFET characteristics changed by introducing hBN under graphene. Incorporation of hBN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 58 publications
1
14
0
Order By: Relevance
“…These discrepancies among reported works are likely attributable to differences in the device's design, composition, and manufacturing-highlighting the importance of the standardization of these processes for graphene-based sensors. [61,62] For the present device, however, the characteristic V g,min shifts and the asymmetric mobility changes suggest that modulation of scattering by charged impurities significantly contribute to the charge transport, similar to what was previously reported. [26,63] Although contributions from other effects cannot be fully discounted and further work is still needed to fully elucidate the detection mechanism/s, [64] it is clear that the electronic signal generated from the device can be used for quantitative protein measurements, making this graphene-based immunosensor suitable for future diagnostic applications.…”
Section: Detection Mechanism Elucidationsupporting
confidence: 89%
See 1 more Smart Citation
“…These discrepancies among reported works are likely attributable to differences in the device's design, composition, and manufacturing-highlighting the importance of the standardization of these processes for graphene-based sensors. [61,62] For the present device, however, the characteristic V g,min shifts and the asymmetric mobility changes suggest that modulation of scattering by charged impurities significantly contribute to the charge transport, similar to what was previously reported. [26,63] Although contributions from other effects cannot be fully discounted and further work is still needed to fully elucidate the detection mechanism/s, [64] it is clear that the electronic signal generated from the device can be used for quantitative protein measurements, making this graphene-based immunosensor suitable for future diagnostic applications.…”
Section: Detection Mechanism Elucidationsupporting
confidence: 89%
“…Table 1 lists some representative works showing that the same type of analyte could induce different electronic responses from graphene. These discrepancies among reported works are likely attributable to differences in the device's design, composition, and manufacturing—highlighting the importance of the standardization of these processes for graphene‐based sensors . For the present device, however, the characteristic V g,min shifts and the asymmetric mobility changes suggest that modulation of scattering by charged impurities significantly contribute to the charge transport, similar to what was previously reported .…”
Section: Resultsmentioning
confidence: 99%
“…200,209 Besides graphene, other 2D materials have also been incorporated into ISFET devices, such as MoS 2 , black phosphorus, and h-BN. 210,211 The key to making these devices commercially viable is to ensure that there exists minimal device-to-device variability for a chosen low-cost, high-throughput fabrication method. Additionally, the storage conditions, shelf life, and multi-usability of the sensors need to be methodically studied and optimized to extend their applicability.…”
Section: Biosensing and Biomedical Applicationsmentioning
confidence: 99%
“…By measuring the shift of the threshold voltage, the device was able to effectively measure potassium concentrations between 10 nM and 1 mM. This LoD is 100× lower than that of commercially available ISEs and 10× lower than that of a commercially available ISFET. , Besides graphene, other 2D materials have also been incorporated into ISFET devices, such as MoS 2 , black phosphorus, and h-BN. , The key to making these devices commercially viable is to ensure that there exists minimal device-to-device variability for a chosen low-cost, high-throughput fabrication method. Additionally, the storage conditions, shelf life, and multi-usability of the sensors need to be methodically studied and optimized to extend their applicability.…”
Section: Biosensing and Biomedical Applicationsmentioning
confidence: 99%
“…ReS 2 FET was also reported to form an EG ISFET with Al 2 O 3 as the sensing layer. To achieve a higher pH sensitivity, different attempts, like the dual gate device structure, have been applied for ISFET to achieve a super-Nernst pH sensitivity. However, it has been reported that the theoretical lower limit of pH resolution does not improve for double-gated sensors . Though the use of high- k metal oxides as sensing layer may provide high sensitivity, they likely suffer from obvious drift during pH measurement.…”
Section: Introductionmentioning
confidence: 99%